Investigation of acquisition of the UWB signals based on BP neural network - YANG Zhi-hua1; ZHANG Qin-yu1; CHEN Ping2; XU Hong-guang1 (Tongxin xuebao, 2005)
A new method based on BP neural networks was proposed here to implement the fast acquisition of UWB signals with the condition of low SNR.The BP neural network was used to match the extreme short pulse in this study.It could improve the performance of the acquisition efficiently.The feasibility and efficiency of the new method were discussed.The influence of the SNR in UWB system was analyzed.The simulation results highly indicate the usefulness of the method pointed out in this study.